IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS (SDGS) LIFE ON LAND DALAM PENGEMBANGAN PUPUK ORGANIK DI DESA KEPANJEN - Permatasari, Yovita Dyah; Marwiyah, Syarifatul; Dasuki, Mohammad; Mu'awwanah, Uliyatul; Hayati, Irma Nur; Bukhori, M. Imam (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2025)
In implementing PkM-BR AI-falah As-sunniyyah university of Kencong Jember, students are required to increase their sense of sensitivity to the community and analyze what is happening in the community. and inorganic (chemical) pesticides can cause wear and degradation of agricultural land. This damage can interfere with land function and soil fertility, thus affecting the sustainability and value of the land. This condition, if left unchecked for a long time, can cause the quality and productivity of farmers to decline. One that can be applied as well as an effort to achieve sustainable development goals is through changing the inorganic (chemical) planting system to an organic planting system. In the future, and finally able to improve the standard of living of farmers' welfare, indirectly the use of organic fertilizers applied to farmers answers the objectives of the Sustainable Development Goals (SDGs) that have been proclaimed by the government, especially number 15, namely Life on land. The objectives of the PkM-BR Al-Falah As-sunniyah university of Kencong Jember student work program are, 1) Increasing the participation of farmer groups in Kepanjen Village in the management of organic fertilizer planting systems, 2) Hands-on training on the manufacture of liquid organic fertilizer; 3) Improving the quality of agricultural production. The type of data collected is primary data and the methods used in this activity are counseling about the importance of sustainable land functions, the importance of maintaining ecosystem balance, the benefits of using organic fertilizers, hands-on practical training on the use of liquid organic fertilizers, the application of liquid organic fertilizer systems in rice fields. The activity is in collaboration with the Gumkmas Agriculture Office (Tun ToT CSA BPP). The support of the Kepanjen Village apparatus, farmer groups, community leaders, and farmers in Krajan Hamlet, Kepanjen Village for the organic fertilizer planting system is very high, this is evidenced by the direct participation of these elements in the process of initial extension activities to the application of the organic fertilizer system. The conclusion from the application of the organic fertilizer planting system is that the production cost of the organic fertilizer planting system is cheaper than the inorganic (chemical) fertilizer planting system.